Checklist of Yunnan Pieridae (Lepidoptera: Papilionoidea) with nomenclature and distributional notes - Hu, Shao-Ji; Inayoshi, Yutaka; Lamas, Gerardo; Zhang, Xin; Duan, Kuang (Zootaxa, 2026)
This article reports a checklist of the Pieridae of Yunnan and is presented with distributional and taxonomic notes. In total, 87 species are confirmed their distribution in Yunnan with 61 in Pierinae, 23 in Coliadinae, and three in Dismorphiinae. Delias belladonna yedanula Frustorfer, 1910 is synonymised with Delias belladonna var. adelma Mitis, 1893 (syn. nov.) based on overlapping distribution range and indistinguishable morphological characters. Male and female genitalia of Gandaca harina (Horsfield, 1829) are illustrated to support the establishment of subtribe Gandacina Grishin, 2023, which was done originally based on molecular evidence. Eurema simulatrix sarinoides (Evans, 1927) is confirmed as the valid name representing the population in S. Yunnan after literature and type specimen analyses. A Lectotype in the Natural History Museum (London, UK) was designated for both Terias lacteola sarinoides Evans, 1927 and for Eurema simulatrix stockleyi Talbot, 1939, which fixes the name sarinoides to the taxon as the valid subspecies name while making stockleyi its junior objective synonym (syn. nov.). Dercas nina Mell, 1913 and Pontia butleri (Moore, 1882) are recorded for the first time in Yunnan, with the specimens and male genitalia illustrated. In addition, 23 taxa that require further confirmation of their presence in Yunnan and those that do not occur in Yunnan are enumerated after the list.